Partisipasi Masyarakat dalam Melestarikan Wilayah Pesisir di Desa Selibata-Bata Kabupaten Kepulauan Aru - Elfis Rungun; Grystin Djein Sumilat; Jolanda Esther Kaihatu; Fonny Rewah (Fakultas Ilmu Sosial dan Hukum, 2023)
This research aims to describe community participation in preserving coastal areas, focusing on thought, energy, financial, and social participation. Research using qualitative descriptive methods Data analysis techniques include stages of reduction, presentation, and conclusion. Research results: The Selibata-bata village government has planned, implemented programs, and supervised coastal area conservation activities. The government and society collaborate in conservation activities. The community took the initiative to form small groups, and the village government coordinated the implementation. Mindful participation is the presence of direction, advice, or appeals from the village government to the community to get involved in activities supporting program implementation. There is readiness for participation by people who care about program implementation and environmental concerns, but some people don't care.